2009
DOI: 10.2105/ajph.2008.139303
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequality in Exposure to Bullying During Adolescence: A Comparative, Cross-Sectional, Multilevel Study in 35 Countries

Abstract: There is socioeconomic inequality in exposure to bullying among adolescents, leaving children of greater socioeconomic disadvantage at higher risk of victimization. Adolescents who attend schools and live in countries where socioeconomic differences are larger are at higher risk of being bullied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
221
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(255 citation statements)
references
References 42 publications
19
221
2
13
Order By: Relevance
“…7 To calculate the sample size, the following parameters were considered: student population at the school equal to 571 students, prevalence of the outcome (occurrence of three or more episodes of bullying known in the last 30 days equal to 50%), sampling error of five percentage points and 95% confidence interval (α=0.05). In view of the adjustment for a finite population and adding 15% for possible losses or refusals, the final sample consisted of 232 students.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 To calculate the sample size, the following parameters were considered: student population at the school equal to 571 students, prevalence of the outcome (occurrence of three or more episodes of bullying known in the last 30 days equal to 50%), sampling error of five percentage points and 95% confidence interval (α=0.05). In view of the adjustment for a finite population and adding 15% for possible losses or refusals, the final sample consisted of 232 students.…”
Section: Methodsmentioning
confidence: 99%
“…6 A cross-cultural research developed in 35 European and North American countries identified a prevalence of victimization ranging between 4.1% and 36.3%. 7 In Brazil, in the National School Health Survey (PeNSE -2012), it was identified that 7.2% of the investigated students affirmed that they were frequent victims and 20.8% practiced some kind of bullying against colleagues. 8 The high occurrence and frequency rates of bullying, associated with the different negative consequences it entails for the victims, witnesses and aggressors' teaching-learning process, health and quality of life, contributes for bullying to be considered a public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…60 An additional 25% to 30% of early deaths are thought to be attributable to either inadequacies in medical care 3 or socioeconomic circumstances, many of which are known to contribute to health care-related disparities. [61][62][63][64][65][66][67] Beyond its strong association with later risk-taking and generally unhealthy lifestyles, it is critically important to underscore the extent to which toxic stress in early childhood has also been shown to cause physiologic disruptions that persist into adulthood and lead to frank disease, even in the absence of later healththreatening behaviors. For example, the biological manifestations of toxic stress can include alterations in immune function 68 and measurable increases in inflammatory markers, [69][70][71][72] which are known to be associated with poor health outcomes as diverse as cardiovascular disease, 69,70,73 viral hepatitis, 74 liver cancer, 75 asthma, 76 chronic obstructive pulmonary disease, 77 autoimmune diseases, 78 poor dental health, 72 and depression.…”
Section: Toxic Stress and The Developing Brainmentioning
confidence: 99%
“…Bullying of adolescents by their peers has been shown to be a significant problem around the world [1,2]. Recent studies from more than 60 countries with a wide range of income levels have found that approximately 1 of every 3 early adolescents has been a victim of bullying [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from more than 60 countries with a wide range of income levels have found that approximately 1 of every 3 early adolescents has been a victim of bullying [1,2]. School bullies are students who purposely target another student, a victim, for recurrent psychological and/ or physical attacks, which may take the form of hitting, kicking, pushing, name calling and teasing, among others [3].…”
Section: Introductionmentioning
confidence: 99%